2005
DOI: 10.1074/jbc.m500434200
|View full text |Cite
|
Sign up to set email alerts
|

31P NMR and Genetic Analysis Establish hinT as the Only Escherchia coli Purine Nucleoside Phosphoramidase and as Essential for Growth under High Salt Conditions

Abstract: Eukaryotic cells encode AMP-lysine (AMP-N-⑀-(N-␣acetyl lysine methyl ester) 5-phosphoramidate) hydrolases related to the rabbit histidine triad nucleotidebinding protein 1 (Hint1) sequence. Bacterial and archaeal cells have Hint homologs annotated in a variety of ways, but the enzymes have not been characterized, nor have phenotypes been described due to loss of enzymatic activity. We developed a quantitative 31 P NMR assay to determine whether Escherichia coli possesses an adenosine phosphoramidase activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
82
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(85 citation statements)
references
References 38 publications
(57 reference statements)
2
82
1
Order By: Relevance
“…Construction of Plasmids-The DHFR fusion protein was constructed based on the pJLCF15DmH plasmid template previously constructed in our laboratory (2,26). The pJLCF15DmH plasmid encodes a fusion protein containing a FLAG peptide at the N terminus of L54F-E. coli DHFR, linked by a 15-amino acid linker to hHint1.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Construction of Plasmids-The DHFR fusion protein was constructed based on the pJLCF15DmH plasmid template previously constructed in our laboratory (2,26). The pJLCF15DmH plasmid encodes a fusion protein containing a FLAG peptide at the N terminus of L54F-E. coli DHFR, linked by a 15-amino acid linker to hHint1.…”
Section: Methodsmentioning
confidence: 99%
“…In the first step, the active site is nucleotidylated by nucleophilic attack at the substrate phosphorous by a conserved active site histidine (His 112 for hHint1 (6). X-ray crystal structure and size exclusion chromatography analyses have revealed that hHint1 exists as a homodimer (2,23,24). Similar to other homodimeric enzymes, such as bacterial alkaline phosphatase, each monomer contains a well separated active site that does not participate in the dimer interface (25).…”
mentioning
confidence: 99%
See 3 more Smart Citations